Perancangan Sistem Reservasi dan Penjadwalan Lapangan Futsal Berbasis Web di Tembilahan - Muhammad Ari Ardana; Fitri Yunita (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
The development of information technology has encouraged various business sectors to use digital systems to improve service quality, including futsal court rental businesses. The process of reservation and court scheduling, which is still done manually, often causes problems, such as scheduling errors, double bookings, and difficulties in delivering information to customers. This study aims to design a Web-Based Futsal Court Reservation and Scheduling System in Tembilahan to increase the efficiency of court rental management and make it easier for customers to make bookings. The method used in this study is the Waterfall method, which includes stages of requirements analysis, system design, implementation, testing, and maintenance. The system is developed based on the web with main features such as court data management, schedule management, online reservations, booking confirmations, and transaction reports. The research results show that the designed system can help managers organize rental schedules more effectively, reduce the risk of scheduling conflicts, and improve the speed and accuracy of services to customers. Besides that, customers can book the fields online more easily, quickly, and accurately. Therefore, this system can be a digital solution that supports improving service quality and operational efficiency for futsal field rental businesses in Tembilahan.